CHALLENGES TO CHRISTIAN MARRIAGE AND FAMILY LIFE IN ASIA TODAY: A Personal Reflection - Fernando, Mervyn (Asian Horizons, 2013)
The largest segment of human relationships in human society is constituted by marriage and family. Not only is marriage and the rearing of children the primary pre-occupation of the vast majority of the adult population of the world at any given point of time, but also the success of the enterprise has a critical impact both on personal happiness and social well-being. For this reason alone the well-being of marriage and family life should take high priority in the policies and plans of both Church and State.